2011
DOI: 10.1091/mbc.e10-06-0499
|View full text |Cite
|
Sign up to set email alerts
|

The proteomics of quiescent and nonquiescent cell differentiation in yeast stationary-phase cultures

Abstract: Starved yeast cultures differentiate into quiescent (Q) and nonquiescent (NQ) cell fractions. The yeast GFP-fusion library (4159 strains) and high-throughput flow cytometry were used to study this process. This showed significant metabolic and physiologic differences between Q/NQ cells and provided new tools for studying their differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(139 citation statements)
references
References 56 publications
6
127
0
1
Order By: Relevance
“…However, by determining the replicative age, we found that these groups are not identical, as the subpopulation of cells with dynamic actin consisted not only of daughter cells but also of mother cells. This situation resembles a new model for the differentiation of Q and NQ cells (61). This recent model shows that cell fate is decided at or before glucose exhaustion.…”
Section: Fig 11mentioning
confidence: 75%
“…However, by determining the replicative age, we found that these groups are not identical, as the subpopulation of cells with dynamic actin consisted not only of daughter cells but also of mother cells. This situation resembles a new model for the differentiation of Q and NQ cells (61). This recent model shows that cell fate is decided at or before glucose exhaustion.…”
Section: Fig 11mentioning
confidence: 75%
“…In starved batch cultures, yeast CLS depends on respiration, not fermentation (67), as long-lived quiescent cells respire nonfermentable carbon that arises from autophagous nonquiescent cells (68). Immobilized yeast under calorie-unrestricted conditions exhibits long CLS in the absence of respiration, which is precluded in ICRs by glucose repression and low O 2 tension.…”
Section: Two-class Sam Reveals Immobilization-specific Changes In Genmentioning
confidence: 99%
“…Peptide N-glycanase activity is difficult to detect in exponentially growing yeast and increases during post-diauxic growth (22), and Png1p abundance is higher in stationary cells than in exponentially growing cells (23). Likewise, Ams1p-dependent p-nitrophenyl-Man hydrolyzing activity is low in exponential yeast cultures and increases during post-diauxic growth (24).…”
mentioning
confidence: 99%